Strategic leadership for responsible artificial intelligence adoption in higher education - Kudzayi S. Tarisayi (CTE Workshop Proceedings, 2024)
Artificial intelligence (AI) has the potential to transform higher education through its potential to improve learning, research, and leadership in colleges and universities. This study aims to identify key themes, challenges, and recommendations related to AI implementation in higher education and leadership. A literature review was supported by 2 LLMs. The results show that AI is being used to personalize teaching, provide formative feedback, identify at-risk students, accelerate research discovery, streamline administrative processes through chatbots, and optimize resource utilization. However, the findings also highlight significant technical, ethical, cultural and resource challenges that institutions must overcome in order to successfully harness AI's enormous potential while mitigating risks. Empowering management through knowledge, funding, and support structures that promote good governance and responsible AI adoption is fundamental to successfully harnessing the enormous but still largely untapped potential of AI.